Influence of eukaryotic translation initiation factor 6 on non–small cell lung cancer development and progression. (September 2018) - Gantenbein, Nadine; Bernhart, Eva; Anders, Ines; Golob-Schwarzl, Nicole; Krassnig, Stefanie; Wodlej, Christina; Brcic, Luka; Lindenmann, Joerg; Fink-Neuboeck, Nicole; Gollowitsch, Franz; Stacher-Priehse, Elvira; Asslaber, Martin; et al.
Abstract: Non–small cell lung cancer (NSCLC) is the leading cause of cancer-related death worldwide. Dysregulation of protein synthesis plays a major role in carcinogenesis, a process regulated at multiple levels, including translation of mRNA into proteins. Ribosome assembly requires correct association of ribosome subunits, which is ensured by eukaryotic translation initiation factors (eIFs). eIFs have become targets in cancer therapy studies, and promising data on eIF6 in various cancer entities have been reported. Therefore, we hypothesised that eIF6 represents a crossroad for pulmonary carcinogenesis. High levels of eIF6 are associated with shorter patient overall survival in adenocarcinoma (ADC), but not in squamous cell carcinoma (SQC) of the lung. We demonstrate significantly higher protein expression of eIF6 in ADC and SQC than in healthy lung tissue based on immunohistochemical data from tissue microarrays (TMAs) and on fresh frozen lung tissue. Depletion of eIF6 in ADC and SQC lung cancer cell lines inhibited cell proliferation and induced apoptosis. Knockdown of eIF6 led to pre-rRNA processing and ribosomal 60S maturation defects. Our data indicate that eIF6 is upregulated in NSCLC, suggesting an important contribution of eIF6 to the development and progression of NSCLC and a potential for new treatment strategies against NSCLC. Highlights: eIF6 is overexpressed in non–small cell lung cancer and is associated with worse overall survival in adenocarcinoma. Knockdown of eIF6 in lung cancer cells reduces proliferation and induces apoptosis. Depletion of eIF6 leads to pre-rRNA processing and ribosomal 60S maturation defects.